Past, Place and Paint: A Neighbourhood Mural Project in Suburban Buenos Aires - DuBois, Lindsay (Anthropologica, 2022)
This article discusses the creation of a mural by the neighbourhood history workshop in a working-class district of Buenos Aires. The mural was chosen as a way of giving immediacy and visibility to memories of three distinct intervals in the history of the neighbourhood, the periods before, during and after military rule. In creating the mural, participants were able to re-establish some of the community solidarity lost during the era when community leaders were subject to repression and "disappearance" and give voice to some of the insecurities of the present. The mural portrays some surprising presences and absences in the collective memory of the different phases of the neighbourhood’s existence and points to ways in which old and new members of the community can work toward a common future.